(untitled) (Journal of the College of Languages (JCL), 2019)
Nineteenth century Gothic literature was deeply concerned with the threats against masculinity. Perhaps one of the most important changes that happened at that time was the emergence of the New Woman model which posed a great threat against masculinity and the male role in the Victorian society. Bram Stoker’s Dracula (1897) portrays female characters who embody this transition in female roles from the domestic wife to the New Woman. This paper focuses on the female characters Mina Murray and Lucy Westenra, their roles in their society, and the different fates they face at the end of the novel, with special focus on Mina’s transformation to the model of the New Woman.